Benefits of Using Experiential Learning Based Electronic Modules to Facilitate Students Concierge Learning in Vocational High Schools - Anita Winandari; Leo Agung Sutimin; Triana Rejekiningsih (Journal of Education Technology, 2022)
Changes in the learning paradigm also contribute to the learning process, such as the use of learning media. Learning media and teaching materials should be integrated with technological developments. Electronic modules or E-Modules are one of the media that can be accessed at any time by students with the help of technological devices. This study aims to identify the various benefits of electronic modules (E-modules) according to the views of students. This research is included in descriptive qualitative research, with research subjects namely students majoring in Tourism class XII Vocational High School with a total of 140 students. Data collection techniques were surveys and interviews, the instruments were questionnaires and interview guidelines. The results of the study were then analyzed using interactive analysis which went through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that there are benefits from the use of experiential learning-based electronic modules, where 94% of students have used e-modules, students are interested because the electronic modules can show learning practice videos. Through the results of this study, it is hoped that it can be a reference for teachers to be able to develop similar electronic media.